The hygiene hypothesis: immunological mechanisms of airway tolerance. (October 2018) - Haspeslagh, Eline; Heyndrickx, Ines; Hammad, Hamida; Lambrecht, Bart N
Highlights: Microbial and environmental signals set tonic activation status of barrier tissues. Signaling from barrier tissues licenses dendritic cells to induce T helper 2 cells. Pulmonary immune system in early-life prone to asthma development. Mechanistic understanding needed to translate epidemiological findings in therapies. Abstract : The hygiene hypothesis was initially proposed as an explanation for the alarming rise in allergy prevalence in the last century. The immunological idea behind this hypothesis was a lack of infections associated with a Western lifestyle and a consequential reduction in type 1 immune responses. It is now understood that the development of tolerance to allergens depends on microbial colonization and immunostimulatory environmental signals during early-life or passed on by the mother. These environmental cues are sensed and integrated by barrier epithelial cells of the lungs and possibly skin, which in turn instruct dendritic cells to regulate or impede adaptive T cell responses. Recent reports also implicate immunoregulatory macrophages as powerful suppressors of allergy by the microbiome. We propose that loss of adequate microbial stimulation due to a Western lifestyle may result in hypersensitive barrier tissues and the observed rise in type 2 allergic disease.